Characteristics of Patients With Complex Limb Pain Evaluated Through an Interdisciplinary Approach Utilizing Magnetic Resonance Neurography - Johnson, Emily M.; Yoon, Daehyun; Biswal, Sandip; Curtin, Catherine; Fox, Paige; Wilson, Thomas J.; Carroll, Ian; Lutz, Amelie; Tawfik, Vivianne L. (Frontiers in Pain Research, 2021)
Patients with persistent complex limb pain represent a substantial diagnostic challenge. Physical exam, and tests such as nerve conduction, are often normal even though the patient suffers from severe pain. In 2015, we initiated a team-based approach to evaluate such patients. The approach included physicians from several specialties (Anesthesiology/Pain Medicine, Radiology, Plastic Surgery, Neurosurgery) combined with the use of advanced imaging with Magnetic Resonance Neurography (MRN). This preliminary case series discusses MRN findings identified in patients with previously difficult-to-diagnose peripheral limb pain and describes how this combination of approaches influenced our diagnosis and treatment plans. We extracted demographics, patient characteristics, presenting features, diagnostic tests performed, treatments provided, referral diagnosis and the diagnosis after interdisciplinary team evaluation from patient charts. We evaluated MRN and electrodiagnostic studies (EDX) ability to identify injured nerves. We compared abnormal findings from these diagnostics to patient reported outcome after ultrasound-guided nerve block. A total of 58 patients, 17 males and 41 females, were identified. The majority of patients presented with lower extremity pain (75%) and had prior surgery (43%). The most commonly identified abnormality on MRN was nerve signal alteration on fluid sensitive sequences, followed by caliber change and impingement. Comparing the outcome of diagnostic nerve blocks with abnormal nerve findings on MRN or EDX, we found that MRN had a sensitivity of 67% and specificity of 100% while for EDX it was 45 and 0%, respectively. After interdisciplinary discussion and imaging review, a more specific diagnosis was produced in 78% of evaluated cases opening up additional treatment pathways such as nerve-targeted surgery, which was performed in 36% cases. This descriptive case series demonstrates that a majority of patients evaluated by our team for complex limb pain were women with lower extremity pain resulting from surgery. In addition, an interdisciplinary team evaluation and the use of the moderately sensitive but highly specific MRN imaging modality resulted in a change in diagnosis for a majority of patients with complex limb pain. Future studies investigating patient outcomes after diagnosis change are currently underway based on the findings of this preliminary study.